2014
DOI: 10.3382/ps.2013-03672
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal expression patterns of doublesex and mab-3 related transcription factor 1 in the chicken developing gonads and Müllerian ducts

Abstract: Sex of birds is genetically determined by the inheritance of sex chromosomes (ZZ for male and ZW for female), and the Z-linked gene named doublesex and mab-3 related transcription factor 1 (DMRT1) is a candidate sex-determining gene in avian species. However, the mechanisms underlying sex determination in birds are not yet understood, and the expression patterns of the DMRT1 protein in urogenital tissues have not been identified. In the current study, we used immunohistochemistry to investigate the detailed ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
0
11
1
Order By: Relevance
“…Although the spatiotemporal expression pattern of the DMRT1 protein was previously reported (Omotehara et al, ), further observations in this study revealed that it was asymmetric between the left and right developing male gonads. The DMRT1 protein was detectable in the male indifferent gonad as early as E4.5 (HH25) as previously described (Omotehara et al, ), and in addition, we found its expression not only in pre‐Sertoli cells in the medulla of the gonad but also in the accumulated cortical cells in the left gonad, especially at the ventral region (Fig. A,B).…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…Although the spatiotemporal expression pattern of the DMRT1 protein was previously reported (Omotehara et al, ), further observations in this study revealed that it was asymmetric between the left and right developing male gonads. The DMRT1 protein was detectable in the male indifferent gonad as early as E4.5 (HH25) as previously described (Omotehara et al, ), and in addition, we found its expression not only in pre‐Sertoli cells in the medulla of the gonad but also in the accumulated cortical cells in the left gonad, especially at the ventral region (Fig. A,B).…”
Section: Resultscontrasting
confidence: 59%
“…Chicken DMRT1 is linked to the Z chromosome. DMRT1 is strongly expressed in pre-Sertoli cells in the early gonads of males (Smith et al, 2003;Omotehara et al, 2014) and plays a critical role in dictating the gonadal fate: its down-regulation induces ovarian instead of testicular differentiation in the genetically male (ZZ) embryo (Smith et al, 2009), and testis-specific genes are up-regulated by overexpression of DMRT1 in the female (ZW) gonad (Lambeth et al, 2014). In addition, especially in the chicken, DMRT1 is also expressed in the coelomic epithelium and mesenchyme around the M€ ullerian ducts and is necessary for their formation (Omotehara et al, 2014;Ayers et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the cortex does not form based on the CASI process that determines the medullary fate (Zhao et al, 2010). It is known that the Z gene DMRT1, a current candidate as a male primary sex determinant in chicken (Guioli et al, 2014;Lambeth et al, 2014;Smith et al, 2009), is expressed symmetrically in the medulla, but also asymmetrically in the gonad epithelium of ZZ and ZW embryos at the time of sex determination Omotehara et al, 2014). As DMRT1 is not subject to dosage compensation (McQueen and Clinton, 2009), our chimeras show that any differences in DMRT1 expression levels due to gene dosage between female and male somatic cells does not impact cortex formation.…”
Section: Discussionmentioning
confidence: 99%
“…We also checked the expression of DMRT1, a known key factor involved in the mitotic-meiotic switch in mouse (Matson et al, 2010;Zarkower, 2013). In chick, as in the mouse, DMRT1 is expressed normally in the proliferating germ cells in both differentiating ovary and testis and it is downregulated soon after meiosis starts (Guioli et al, 2014;Omotehara et al, 2014). As shown in Fig.…”
Section: Meiotic Entry Of Cortical Germ Cells Is Severely Compromisedmentioning
confidence: 99%
“…It is widely accepted that primary sex-determination in birds is likely to depend on a gene dosage mechanism based on a Z chromosome gene(s) 11 . The most likely candidate gene is the Z chromosome gene DMRT1 12 ; DMRT1 expression is restricted to cells of the gonads and the Mullerian ducts and it is expressed at higher levels in the male than in the female at the time of sex determination 13,14 . In ovo manipulation studies show that a reduction in DMRT1 levels leads to feminisation of the genetically male (ZZ) gonad 15 and that overexpression of DMRT1 leads to masculinisation of the genetically female (ZW) gonad 16 .…”
Section: Introductionmentioning
confidence: 99%